An investigation on university students' perceptions about icebreakers in classrooms / Che Nooryohana Zulkifli and Mohamad Putera Idris - Zulkifli, Che Nooryohana; Idris, Mohamad Putera (Universiti Teknologi MARA, Kedah, 2021)
This study presents the importance of having ice-breaking activities in classrooms and how it can help learners to feel welcome and comfortable as well as it can provide them with a platform to initiate episodes of conversation with others who are first considered strangers to them. Argued by Dixon, Crooks and Henry (2006), icebreakers normally serve as early activities that participants in a particular group take part before any other social relationships could be developed as it could influence one's social presence in a particular setting. Thus, considering this notion, this paper examined the usefulness and effectiveness of ice-breaking activities to learners as part of their learning experience. There are 46 learners cum respondents had undergone three ice-breaking activities before they were asked to answer open-ended questions which are related to the significance of ice breaking and how the activities could help them to socialise and build appropriate network whenever necessary. The main goals of this study are to investigate the learners' point of view about icebreakers to unearth the types of information they usually provide when introducing themselves and to what extent icebreaking activities can help them in their daily interaction in classrooms. The results, however, show that not all respondents felt comfortable and ready to break the ice with those whom they barely knew. Nevertheless, the data proves that to feel less anxious is important whenever the learners are required to engage in any of the classroom activities and this can be done through icebreakers.